Scénario, bande dessinée, film : les romans intermédiaux de Marçal Aquino et Lourenço Mutarelli - Angélica Amâncio (Caravelle)
This paper studies the work of Brazilian writers Lourenço Mutarelli and Marçal Aquino to consider issues related to text and image. The selected works are O grifo de Abdera (“Abdere’s griffin”, 2015), and O Invasor (“The Trespasser”, 2002). To analyze the complexity of these novels we mainly rely on the typology of intersemiotic transposition proposed by Leo H. Hoek and the concept of novelization introduced by Jan Baetens. We also mention the research of Vera Lúcia Follain de Figueiredo, in order to replace the dialogue between literature and cinema in the Brazilian context.